N-acetylcysteine as adjuvant therapy for hospitalized Covid-19 patients: A single-center prospective cohort study - Siamak Afaghi; Negin Moghimi; Nasser Malekpour Alamdari; Fatemeh Sadat Rahimi; Rana Irilouzadian; Farzad Esmaeili Tarki; Morvarid Moghimi; Sara Beshaarat; Hossein Salehi Omran; Anita Karimi (Babol University of Medical Sciences, 2023)
Background: Whilst over two years have passed since the COVID-19 pandemic's emergence, the proper management of the disease remains challenging. N-acetylcysteine (NAC) as a potentially effective therapeutic option has been suggested by studies, while the exact clinical role of this agent is yet to be evaluated. Methods: This prospective case-control study was conducted in a major referral respiratory center in Tehran, Iran. We enrolled 217 patients treated with an intravenous daily dose of 1500 mg NAC as a case group; and 245 control patients who did not receive NAC. Two groups were matched based on other treatments, socio-demographics, medical history, and comorbidities. Results: After ten days of adjuvant therapy with NAC, patients in the NAC group and control group had median room-air SpO2 of 91% and 88%, respectively (P=0.02). Also, the SpO2 to FiO2 ratio had a median of 463 and 421 in the case and control groups, respectively (P=0.01). Furthermore, the case group's hospitalization period was three days shorter (P=0.002). Further, cough, dyspnea, and decreased appetite were reported to have a significantly lower incidence in the case group (P=0.03, 0.001, 0.008). Conclusion: We showed that a daily intravenous dose of NAC in hospitalized COVID-19 patients could shorten the hospital stay and improve some clinical symptoms; however, it does not remarkably improve the risk of ICU admission and the 28 days in-hospital mortality rate.